Utilization of Interactive Multimedia Tools in Enhancing Reading Skills of Primary and Intermediate Learners at Leonardo Barrun Elementary School - Almodal, Nerma (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the utilization of interactive multimedia tools in enhancing the reading skills of primary and intermediate learners at Leonardo Barrun Elementary School in San Jacinto, Masbate. Anchored on Mayer’s Cognitive Theory of Multimedia Learning, Constructivist Learning Theory, and Vygotsky’s Sociocultural Theory of Learning, the study investigated the relationship between teachers’ multimedia utilization and learners’ reading skills. A quantitative descriptive–correlational research design was employed involving 32 elementary teachers handling Grades 1–6. Data were gathered through a validated researcher-made questionnaire that measured the utilization of videos, animations, e-books, and educational applications, as well as learners’ reading skills in terms of vocabulary development, reading comprehension, reading fluency, and critical thinking skills. Frequency count, percentage, weighted mean, ranking, and Pearson Product-Moment Correlation Coefficient were used in analyzing the data. Findings revealed that teachers often utilized videos, animations, and educational applications in reading instruction, while e-books were only sometimes utilized. Learners demonstrated a high level of vocabulary development and moderate levels of reading comprehension, reading fluency, and critical thinking skills. The study further revealed a strong positive and statistically significant relationship between teachers’ utilization of interactive multimedia tools and learners’ reading skills (r = 0.78), indicating that increased multimedia integration contributes positively to learners’ reading performance. The study concluded that multimedia-supported instruction enhances learner engagement and strengthens literacy development among elementary learners. It recommended continuous teacher training, improved technological resources, and the institutionalization of multimedia-enhanced reading programs to further improve reading instruction and learner outcomes. The study supports Sustainable Development Goal (SDG) 4 on Quality Education by promoting inclusive and effective literacy instruction through technology-enhanced learning. It also aligns with SDG 9 on Industry, Innovation and Infrastructure through the integration of digital tools in classroom instruction. The study contributes to educational and technological sustainability by encouraging innovative instructional practices that strengthen literacy development, learner participation, and digital competence in elementary education.